Archimede Solar Energy Molten Salt Parabolic Trough Demo Plant: A Step Ahead towards the New Frontiers of CSP. (May 2015) - Maccari, A.; Bissi, D.; Casubolo, G.; Guerrini, F.; Lucatello, L.; Luna, G.; Rivaben, A.; Savoldi, E.; Tamano, S.; Zuanella, M.
Abstract: Since July 2013 the first stand-alone Molten Salt Parabolic Trough (MSPT) plant, located adjacent to the Archimede Solar Energy (ASE) manufacturing plant in Massa Martana (Italy), is in operation. After one year of operation, the management of the ASE demonstration plant has shown that MSPT technology is a suitable and reliable option. Several O&M procedures and tests have been performed, always with very good results confirming that this approach can be easily scaled up to realize standard size CSP plants without any concern, if the plant design takes into account molten salt peculiarities. In this paper a brief description of the plant and the overall and main plant operation figures will be presented.